1994
DOI: 10.1063/1.111023
|View full text |Cite
|
Sign up to set email alerts
|

White light-emitting organic electroluminescent devices using the poly(N-vinylcarbazole) emitter layer doped with three fluorescent dyes

Abstract: White light-emitting electroluminescent devices were fabricated using poly(N-vinylcarbazole) (PVK) as a hole-transporting emitter layer and a double layer of 1,2,4-triazole derivative (TAZ) and tris(8-quinolinolato)aluminum(III) complex (Alq) as an electron transport layer. The PVK layer was doped with fluorescent dyes such as blue-emitting 1,1,4,4-tetraphenyl-1,3-butadiene, green-emitting coumarin 6, and orange-emitting DCM 1. A cell structure of glass substrate/indium-tin-oxide/doped PVK/TAZ/Alq/Mg:Ag was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
355
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(362 citation statements)
references
References 18 publications
2
355
0
5
Order By: Relevance
“…[6,7] These properties could be very important for example when trying to achieve white emission, one of the most important developments in the field of polymer emitting devices, where complex mixtures are used in order to gain broad white emission and balanced electron and hole transport within a single "emission" layer. [8,9,10,11] Polyfluorenes have been extensively studied for display applications, owing to their pure blue and efficient electroluminescence coupled with a high charge carrier mobility and good processability. [12] Several studies have been reported, including mixing of polyfluorenes with different emissive materials and applying them in single or multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] These properties could be very important for example when trying to achieve white emission, one of the most important developments in the field of polymer emitting devices, where complex mixtures are used in order to gain broad white emission and balanced electron and hole transport within a single "emission" layer. [8,9,10,11] Polyfluorenes have been extensively studied for display applications, owing to their pure blue and efficient electroluminescence coupled with a high charge carrier mobility and good processability. [12] Several studies have been reported, including mixing of polyfluorenes with different emissive materials and applying them in single or multiple layers.…”
Section: Introductionmentioning
confidence: 99%
“…Organic light-emitting diodes (OLEDs) are already widely used in display applications due to their capability to produce light across the visible spectrum [424] and tunability of the OSCs optical and electrical properties through molecular design [425]. However, their compatibility with flexible substrates and cheap fabrication methods points to future applications in solid-state lighting and flexible displays [7,426,427].…”
Section: Organic Light-emitting Diodes (Oleds)mentioning
confidence: 99%
“…e first report on white OLEDs dates back to 1994, when a Japanese group combined red, green and blue (RGB) laser dyes in a common matrix and achieved light emission over a broad spectral range [4]. Despite its simplicity in preparation, achieving white light emission with good and stable colour quality in this way is not that straightforward, because charge recombination and energy transfer processes between the different dyes need to be well controlled.…”
Section: White Oledsmentioning
confidence: 99%